Role of permeability barriers in alluvial hydromorphic palaeosols: The Eocene Pondaung Formation, Myanmar. Issue 2 (29th August 2013) - Licht, Alexis; Cojan, Isabelle; Caner, Laurent; Soe, Aung Naing; Jaeger, Jean‐Jacques; France‐Lanord, Christian; Mountney, Nigel
Abstract This study examines the lateral distribution of hydromorphy in the fine‐grained alluvial deposits of the Eocene Pondaung Formation, central Myanmar. Through detailed outcrop analysis and using a combined sedimentological and pedological approach, this study proposes a reconstruction of Pondaung overbank floodplain palaeoenvironments. The variations of hydromorphic features in the different overbank sub‐environments are then discussed and used to build a model of hydromorphic variability in alluvial deposits. Two main architectural associations with distinctive lithofacies and pedogenic features were identified, corresponding to different sub‐environments: heterolithic deposits and extensive mudstone successions. The heterolithic deposits display variegated fine‐grained lithofacies and contain poorly developed palaeosols with gley and vertic features, which are interpreted to reflect a seasonal wetlands landscape, developed in actively aggrading avulsion belts. Extensive mudstone successions with Vertisols that locally exhibit mukkara‐style pseudogley features are interpreted to represent a distal open‐forested environment. The palaeosols of both sub‐environments display dense local hydromorphic variations they are also characterized by a gradual shift from gley‐dominated to pseudogley‐dominated features with increasing distance from the avulsion belt. The clay‐dominated lithology of the floodplain parent material, which forms numerous subsurface permeability barriers, is shown to have acted as a fundamental control in limiting water‐table dynamics in coarse‐grained parts of the succession, thereby favouring hydromorphic variability. Palaeosol sequences of the Pondaung Formation contrast with the soil‐landscape associations described in other studies and provide an alternative model with which to account for the hydromorphic variability in poorly drained, alluvial soils. The model proposed as an outcome of this study demonstrates that hydromorphic variations can be dramatic in floodplains where permeability barriers are numerous. Further, the model stresses the importance of undertaking detailed lateral palaeosol analyses prior to making interpretations regarding hydromorphic variability.